Non-metastatic Ewing’s sarcoma family of tumors arising from head and neck: a single institution experience - Goyal, Shikha; Biswas, Ahitagni; Mohanti, Bidhu K.; Bakhshi, Sameer (Therapeutic Radiology and Oncology, 2019)
Background: Head and neck peripheral primitive neuroectodermal tumors (pPNET) are uncommon and require multimodality management including significant contribution from radiation therapy. We attempted to evaluate the outcome of non-metastatic pPNET of head and neck in our institution. Methods: We retrospectively reviewed the treatment records of 21 patients treated from 2004–2009, and describe their outcome in this report. Results: There were 13 males and 8 females, with median age of 13 years (range, 3–31 years). The most common sites were mandible (N=7), maxilla (N=5), orbit (N=4), parotid (N=2), supraclavicular region (N=2) and nasal cavity (N=1). Treatment included chemotherapy (N=21), radiotherapy (N=21) and surgery (N=5). Chemotherapy regimens were VAC/IE (N=19) and modified St Jude’s (N=2). 3D conformal radiotherapy was used, mean dose being 55 gray (range, 30–60 gray). Two patients did not complete planned treatment. Treatment responses included complete response (N=13), partial response (N=5), stable disease (N=1) and progressive disease (N=2). One patient developed local recurrence following complete response, 24.23 months following diagnosis. Mean follow-up duration was 26.7 months (range, 7.37 to 77.47 months). At last follow-up, 12 patients were disease-free, 6 were alive with disease and 1 patient had died of unrelated cause. Conclusions: Head and neck is a rare site for pPNET. Both surgery and radiotherapy pose challenges due to dose-limiting structures in immediate vicinity of tumor, difficulty in performing extensive resection and cosmesis issues. Combined modality treatment is the best curative option.